Proposal of an index for screening and for monitoring of swine atrophic rhinitis - Brito, José R. Feitosa; Piffer, Itamar A.; Brito, Maria A. V. P.; Sobestiansky, Jurij (Pesquisa Agropecuaria Brasileira, 1993)
An index for evaluation of swine atrophic rhinitis was proposed based on the scores of nasal burbinate atrophy. The index is the weighted mean of the nasal turbinate scores. Data from four herds with 35, 120, 168 and 220 sows were analysed over a period of more than a year. Nasal turbinates were scored from zero to three according to the severity of damage. Clinical signs of atrophic rhinitis were also considered in animals of each herd. The following interpretation is suggested for the index values: herds with normal to slight atrophic rhinitis 0 to 0.30; slighty affected, 0.31 to 0.45; and moderately to severely affected, 0.46 to 3.0.